John Thompson Ford papers - Ford, John Thompson, 1829-1894.; Ford, Annie; Ford, Lizzie
Correspondence, play scripts and other writings, subject files, playbooks, playbills, scrapbooks, and other papers relating to Ford's life and work as a theater manager in the last half of the nineteenth century. Documents his interaction with major theatrical figures of the period; the productions featured at his theaters in Baltimore, Md., Philadelphia, Pa.; Charleston, S.C., Alexandria, Va., Richmond, Va., and Washington, D.C.; the assassination of Abraham Lincoln by the actor John Wilkes Booth at Ford's Theatre in Washington, D.C.; and Ford's political career in Baltimore, Md. Subjects include the Holliday Street Theatre and Grand Opera House in Baltimore, Md., and Ford's charitable activities and management of Gilbert and Sullivan productions. Includes seating plans for Ford's Theatre and writings, notes, and scrapbooks of his daughters, Annie E. Ford and Lizzie Ford. Correspondents include Edwin Booth, Edwin Forrest, Joseph Jefferson, Clifton W. Tayleure, and William Winter.
Library of Congress Prints and Photographs Division.
Theater executive and dramatist.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Booth, Edwin, -- 1833-1893 -- Correspondence; Booth, John Wilkes, -- 1838-1865.; Forrest, Edwin, -- 1806-1872 -- Correspondence; Gilbert, W. S. -- 1836-1911.; Jefferson, Joseph, -- 1829-1905 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Sullivan, Arthur, -- 1842-1900.; Tayleure, Clifton W., -- -1891 -- Correspondence; Winter, William, -- 1836-1917 -- Correspondence; Ford's Theatre (Washington, D.C.); Grand Opera House (Baltimore, Md.); Holliday Street Theatre (Baltimore, Md.); Charities; Theaters -- Maryland -- Baltimore; Theaters -- Pennsylvania -- Philadelphia; Theaters -- South Carolina -- Charleston; Theater -- United States; Theaters -- Alexandria -- Richmond; Theaters -- Virginia -- Richmond; Theaters -- Washington (D.C.); Baltimore (Md.) -- Politics and government; Dramatists; Executives